2020
DOI: 10.1111/mpp.12978
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin response induces immunity and fungal pathogen resistance, and modulates trafficking of the PRR LeEIX2 in tomato

Abstract: Plant immunity is often defined by the immunity hormones: salicylic acid (SA), jasmonic acid (JA), and ethylene (ET). These hormones are well known for differentially regulating defence responses against pathogens. In recent years, the involvement of other plant growth hormones such as auxin, gibberellic acid, abscisic acid, and cytokinins (CKs) in biotic stresses has been recognized. Previous reports have indicated that endogenous and exogenous CK treatment can result in pathogen resistance. We show here that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(123 citation statements)
references
References 85 publications
15
108
0
Order By: Relevance
“…As reported previously by us and others, CK was shown to promote fungal disease resistance in plants (21,24). Direct effects of CK on fungal growth and development have not been investigated in depth in plant-free systems, and although a few studies have discussed some effects of CK on fungal pathogen growth (9,10), no mechanisms for CK antifungal activity have yet been reported.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…As reported previously by us and others, CK was shown to promote fungal disease resistance in plants (21,24). Direct effects of CK on fungal growth and development have not been investigated in depth in plant-free systems, and although a few studies have discussed some effects of CK on fungal pathogen growth (9,10), no mechanisms for CK antifungal activity have yet been reported.…”
Section: Discussionmentioning
confidence: 93%
“…CK showed no effect on leakage of nucleic acids and proteins from It has been previously suggested that certain classes of fungi possess CK receptors to be able to "sense plants", a trait posited to have been required for land colonization by fungi (69). We and others have previously demonstrated that plants activate CK signaling upon pathogen attack, and that CK serves as a cue to activate defense responses (21,24,65) (Fig. 7), or S. cerevisiae (Fig.…”
Section: Examination Of Possible Effects Of Ck On Bc Development Revementioning
confidence: 83%
See 2 more Smart Citations
“…fungi, in a mechanism dependent on SA and ET signalling (Gupta et al, 2020). We showed that fungal pathogens cause activation of the tomato CK machinery, and that CK-mediated disease resistance requires pattern recognition receptors.…”
mentioning
confidence: 94%